Polymeric nanocomposites for electromagnetic wave absorption - Huo, Jia; Wang, Li; Yu, Haojie (Journal of materials science, 2009)
The need for protecting human or devices from harm and for keeping something from being detected by other instruments is spawning a world of attention in the development of novel electromagnetic (EM) wave absorption materials. An ideal EM wave absorber is necessary to have light weight, thin thickness, high EM wave absorption, broad width, tunable absorption frequency, and multi-functionality. This article introduces the EM wave absorption mechanism and reviews the development of polymer-based nanocomposites for EM wave absorption, in which polymers act as absorbing components or/and matrixes. And we also summarize the approaches to design the ideal absorber, including introduction of nanostructure, and simultaneous action of both dielectric and magnetic materials with special structure by directly mixing, core–shell or multilayer structure.